Overview of Emergency Preparedness of Nurses in Hospitals in the Face of Disasters - Zahra Ananda; Hasanatun Laili; Mayumi Ershanda; Abdurrozzaq Hasibuan (Journal of Educational Innovation and Public Health, 2024)
This research aims to identify and examine the emergency preparedness of nurses in hospitals in dealing with disasters through the literature review method. Hospitals have an important role in disaster preparedness and management, because they must be able to provide a quick and effective response to emergency situations caused by disasters. Data were collected from articles and national journals published in the last 10 years, using related keywords such as "nurse preparedness", "emergency", "disaster management in hospitals", and "disaster training for nurses". Analysis was carried out on 30 articles that met the inclusion criteria. The research results show that nurses' knowledge of disaster management is still inadequate, even though many have basic knowledge of emergency protocols. Practical skills obtained through training and disaster simulations have a big influence on nurses' preparedness, but opportunities to take part in this training are not evenly distributed. Nurses' perceptions regarding hospital preparedness and themselves show that many feel that hospitals are not fully prepared to face major disasters. Hospital management support and access to relevant information are also important factors influencing nurse preparedness. Recommendations from this research include increasing routine disaster training and simulation programs, developing formal education curricula on disaster management, increasing hospital management support, utilizing information technology for quick access to disaster information, as well as monitoring and evaluating preparedness on a regular basis. By implementing these recommendations, it is hoped that nurses' preparedness in facing disasters can be improved, so that they are able to provide a fast and effective response in emergency situations, as well as improve patient safety.